3D food printing – Asian snacks and desserts. (2022) - Pant, Aakanksha; Zhang, Yi; Kai Chua, Chee; Jia Yao Tan, Justin; Hashimoto, Michinao; Huei Leo, Chen; Hooi Chuan Wong, Gladys; Tan, U-Xuan
Abstract: '3D food printing technology is a rapidly advancing technology offering customization in nutrition, shape, taste and texture. Popular foods can be created in exciting and visually appealing forms through 3DFP. In this paper, we demonstrate the 3D printability of rice flour mixed with chai poh powder to recreate familiar Asian dish, chwee kueh. 3DFP of yam paste and gingko nut was also conducted for orh nee dish recreation. Extrusion printing was the chosen technique to 3D print different shapes. Two commercially available food printers were used to test these two food ink formulations. Further experimentation is required to improve and characterize the food inks with additional ingredients like sugar, oil to achieve better printability as well as taste and texture'.